The Impact of Workplace Spirituallty, Compensation, and Characteristics of Millenial Teachers on Teacher Loyality - Prahara, Rahma Sandhi; Ningrum, Rahmania Widya; Fahmi, Mohammad Farih (Pusat Studi Aswaja An-Nahdliyyah UNISNU Jepara, 2024)
The purpose of this study was to determine the effect of millennial teacher characteristics, compensation, and workplace spirituality on teacher loyalty, an overview/generalization of the research problem. This research uses a mixed-methods approach with a sequential explanation. The study's population consisted of the 52 teachers that work at Taruna Nusa Harapan (TNH) Elementary School. Purposive sampling is the method of sampling that is employed. Results of the research show that workplace spirituality, compensation, and millennial teachers' characteristics all significantly affect teachers' loyalty at TNH Elementary School. This is demonstrated by the calculated F value of 4.034, which is higher than the 2.95 F table value with a 0.028 significance level. At TNH Elementary School, the millennial teacher characteristic variable (X1) has a t-count value of 0.281 and a t-table value of 2.042, indicating that it has a partially zero effect on teacher loyalty. There is a partially significant positive effect for the compensating variable (X2), with a t-count value of 2.837 and a t-table of 2.042. There is a marginally significant positive influence on workplace spirituality (X3), with a t-count value of 2.735 and a t-table of 2.042. The results of R2 (coefficient of determination) of 0.818 or (81.8%) and the remaining 18.2% are influenced by other variables outside this research model. Â